Implementation of the health insurance policy at UPTD Puskesmas Ajangale Bone District - Muh Dandy Rivaldi; Nursalam Nursalam; Maria M Lino (Universitas Nusa Cendana, 2026)
This study aims to analyze the implementation of health services for BPJS Kesehatan beneficiaries at UPTD Puskesmas Ajangale and to identify the factors that hinder its implementation. The research uses a descriptive qualitative approach with data collected through in-depth interviews, observation, and documentation. The analysis is based on the implementation theory developed by George C. Edwards III, which emphasizes four main variables: communication, resources, disposition of implementers, and bureaucratic structure. The findings indicate that the implementation of BPJS health services has been carried out administratively but has not yet operated optimally. Basic health services such as outpatient treatment, immunization, and referral services are available, yet several obstacles remain. Communication between health workers and patients is often ineffective, the number of medical personnel and the availability of medicines are limited, and some health workers still lack a humanistic approach in providing services. In addition, bureaucratic procedures, particularly the referral process, tend to be slow and less responsive to urgent situations. The main factors that hinder the effectiveness of BPJS service implementation include the shortage of health workers, limited development of service information systems, insufficient public education about health service procedures, and administrative processes that are still relatively complex. Overall, the study concludes that although BPJS health services have been implemented, improvements in both structural and operational aspects are still necessary to ensure that health services become more effective, efficient, and equitable for the community. Keywords: Implementation; Health Services; BPJS; Public Health Center; Public Policy